2020
DOI: 10.3390/jcm9041044
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Rare and Harmful Lineages is Associated with Established Rheumatoid Arthritis

Abstract: Objectives: To characterize the gut microbiota profile in rheumatoid arthritis (RA) patients and investigate its association with certain characteristics of RA. Patients and methods: A nested case–control cohort of 40 patients with RA and 40 sex-age matched controls was studied. Subjects with diabetes, with any other inflammatory disease, practicing extreme diets, taking antibiotics, probiotics or under any new treatment for at least three months prior to sampling were excluded. The microbiota composition was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…Gut microbiota is a promising agent for the development of personalized medicine as it collects information about its host, like diet or environmental factors [ 8 ]. Recent evidence suggest that the alteration of gut microbiota may have connection with autoimmune diseases [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gut microbiota is a promising agent for the development of personalized medicine as it collects information about its host, like diet or environmental factors [ 8 ]. Recent evidence suggest that the alteration of gut microbiota may have connection with autoimmune diseases [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The subsequent findings have not been completely consistent across the literature, but a repeated feature has been the increase of Prevotella species in early RA [ 47 , 48 , 49 , 50 ], associated to a relative decrease in the Bacteroides genus [ 48 , 51 ]. The overrepresentation of Prevotella species is usually no longer found in established and treated RA patients [ 52 , 53 , 54 ]. In particular, Prevotella copri raised researcher’s interest, because of worsening arthritis when transferred in mice models [ 47 , 48 ].…”
Section: Gut Microbiota In Ra Development: Is Microbiota the Missimentioning
confidence: 99%
“…Nevertheless, additional immunological studies on human samples (blood, stool, or gut biopsies) are necessary to clarify the mechanism linking P. copri to the onset of RA. Finally, other bacterial species have been associated with human RA, such as Collinsella aerofaciens [ 53 , 54 ]. The latter also worsens arthritis in mice models [ 53 , 54 ], which underlines the fact that there may not be a single bacterial culprit, but probably a complex interplay between several microorganisms and host defenses.…”
Section: Gut Microbiota In Ra Development: Is Microbiota the Missimentioning
confidence: 99%
See 1 more Smart Citation
“…The authors have suggested that it was the GM that influenced autoimmunity and may affect the development of type 1 diabetes [4]. C. aerofaciens may affect the pathogenesis of RA through various mechanisms, for example, by increasing the permeability of the intestinal wall, production of IL-17, and chemotaxis of neutrophils [6].…”
Section: Introductionmentioning
confidence: 99%